Bioavailability for organic chemical bioaccumulation follows the power law. (1st November 2021) - Wang, Rubing; Li, Xinmeng; Xu, Jiahui; Hu, Canyang; Wang, Zhuhua; Chen, Jingwen; Cai, Xiyun
Abstract: Despite the importance of bioavailability for organic chemical bioaccumulation by terrestrial and benthic invertebrates, the principles of bioavailability for organic chemical bioaccumulation remain poorly understood. Here we use large-scale databases with contrasting geographic, compound and organism coverage (from 925 sites, 446 compounds and 184 invertebrate species), and report that bioavailability for organic chemical bioaccumulation follows the power law. It represents that the internal concentration of organic chemicals is the composite power function of the lipid fraction of invertebrates, bulk site concentration of compounds, and organic carbon content of soils/sediments. This law directly links environmental exposures and body burdens of organic chemicals in contaminated sites, and provides a method for enabling case-specific risk assessments of a vast number of organic chemicals and contaminated sites. Our findings may pave the way for translating bioavailability knowledge into risk-oriented regulation of organic chemicals and contaminated sites. Graphical abstract: Image 1 Highlights: Cyclodextrin extraction of PAHs in soils may mimic ingestion behavior of earthworms. The power law explains the similarity and variability nature of bioavailability. The power law links environmental exposures and body burdens of contaminants. The power law provides a method to translate bioavailability science to regulation. Abstract : The power law of organic chemicals governs bioavailability for organic chemical bioaccumulation by terrestrial and benthic invertebrates and provides approaches for bioavailability applications.